Giving Voice to the Voiceless: Probing Current Issues for Student Teachers in EFL Teacher Education Program in Iran - Fatemeh Karimi; Ebrahim Fakhri Alamdari; Mehrshad Ahmadian (National Research University Higher School of Economics, 2021)
The present study attempted to give insight into the features of an effective English as a foreign language (EFL) teacher education program by exploring student teachers' beliefs, ideas, and the challenges they encounter during their teacher education program. The data were collected through several semi-structured focus group interview sessions with a total number of forty-one BA, MA, and PhD students studying teaching English as a foreign language (TEFL) at university. The qualitative grounded theory design was used to analyze the data, and the findings of the study were corroborated with interpretations obtained from the informal observation of several university classes in a TEFL teacher education program in Iran. The inductive analysis of the data resulted in developing the following categories: the challenge of developing the ability to move back and forth from theory to practice, the struggle to establish a professional identity, the quest for the 'self', less-practiced reflective practice, and the missing connection between teacher education programs and schools. The discussion concerning the challenges and issues culminated in implications for EFL teacher education programs through which they can take the issues that student teachers normally experience into account and help them pave the way for an effective EFL teacher education program.